2010
DOI: 10.1159/000320610
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory and Proadhesive Activation of Lymphocytes and Macrophages in Sudden Sensorineural Hearing Loss

Abstract: Even though sudden sensorineural hearing loss (SHL) is a quite frequent disease, the pathogenetic processes leading to it are widely unknown. There is increasing evidence that immunomodulatory cells, especially T lymphocytes, might be involved. Twelve patients with acute SHL and 12 healthy, age-matched individuals were included in this study. In addition to routine blood parameters, plasma levels of tumor necrosis factor alpha (TNF-α), soluble CD40 (sCD40) and sCD40 ligand (sCD40L) were determined by ELISA. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 76 publications
1
36
0
Order By: Relevance
“…10 While some investigators reported that, in an animal model, etanercept has a protective effect on hearing loss, 11 others found it less effective than prednisone, with a greater potential for adverse effects. 4,6,12 In 2 small human studies, levels of TNF in patients with sudden SNHL were found to be elevated in one study of 12 patients, 13 while the other study showed that both corticosteroid-responding and nonresponding patients (total of 30 for both groups together) had lower levels of TNF than controls and concluded that this cytokine does not offer useful information in either prognosis or diagnosis of the disease.…”
Section: Arch Otolaryngol Head Neckmentioning
confidence: 99%
“…10 While some investigators reported that, in an animal model, etanercept has a protective effect on hearing loss, 11 others found it less effective than prednisone, with a greater potential for adverse effects. 4,6,12 In 2 small human studies, levels of TNF in patients with sudden SNHL were found to be elevated in one study of 12 patients, 13 while the other study showed that both corticosteroid-responding and nonresponding patients (total of 30 for both groups together) had lower levels of TNF than controls and concluded that this cytokine does not offer useful information in either prognosis or diagnosis of the disease.…”
Section: Arch Otolaryngol Head Neckmentioning
confidence: 99%
“…1 Although SSNHL is a wellrecognized condition, no standard definition or treatment protocol has been accepted. [3][4][5][6][7][8][9] But none of the theories alone can explain the etiopathogenesis of ISSNHL, which most probably is multifactorial in etiology. 2 A number of theories have been hypothesized to explain the etiopa-thogenesis of ISSNHL, including infectious diseases, vascular occlusion, ruptures in the cochlear membrane, immune mediated mechanisms, and abnormal cellular stress responses within the cochlea.…”
Section: Introductionmentioning
confidence: 99%
“…7,10 It is now clear that the inner ear is not an ''immunologically privileged'' site, and according to recent studies 11,12 there is increasing evidence of immune mediated mechanisms in the etiopathogenesis of ISSNHL. However, some studies have shown the existence of a local immune response within the inner ear, with an enhanced transmigration of immunocompetent cells from the bloodstream.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that WBC counts are a biomarker related to systemic stress and cochlear inflammation [25]. Additionally, several systemic inflammatory processes can be detected by examination of the blood, which may also be a very promising approach for monitoring possible pathogenetic mechanisms associated with SSNHL [26]. In this study, downregulated AGO2 mRNA expression level (I, 11.89±1.15; III, 9.54±1.7) was found in abnormal WBC counts group I and III in comparison with normal WBC counts group II (7.37±2.67).…”
Section: Discussionmentioning
confidence: 99%